Chronic Encapsulated Intracerebral Hematoma Mimicking Malignancy. Issue 4 (November 2015) - Lin, Bon-Jour; Ma, Hsin-I
Abstract : Chronic encapsulated intracerebral hematoma is a rare disease characterized by progressive neurological deficit accompanied with ring-enhancing intracranial mass lesion. A 43-year-old woman presented with weakness over bilateral lower limbs over days. Computed tomography of the brain showed a hypodense parenchymal lesion over the left frontal lobe with mass effect. Magnetic resonance imaging revealed the presence of a peripheral hyperdense with central isointense parenchymal lesion on T1-weighted and T2-weighed images, with surrounding brain edema. The patient underwent craniotomy for excision of lesion under the preoperative impression of brain tumor. The pathologic report was hemorrhagic infarction with marked gliosis. This report highlights that chronic encapsulated intracerebral hematoma is similar to brain tumor in clinical expression and neuroimaging appearance.